Material removal behavior in processing green Al2O3 ceramics based on scratch and edge-indentation tests. Issue 9 (15th June 2019) - Liu, Yayun; Deng, Jianxin; Yue, Hongzhi; Duan, Ran; Li, Xuemu; Ehmann, Kornel
Abstract: To understand material removal behavior in green ceramics processing, as one of the essential elements for improving processing quality, scratch and edge-indentation tests were performed to ascertain the material removal mode and to characterize the machined surfaces. The results revealed that scratch and edge-indentation tests provide new alternative methods to study the processing behaviors of green Al2 O3 ceramics. Prediction models for the depth of the scratch groove, and for the peak cutting forces corresponding to the depth of cut were formulated. It has been shown that the mode of green ceramic material removal is transgranular fracture consisting of a combination of ploughing and ductile cutting. Ploughing dominates under smaller depths of cut and larger scratch velocities, while ductile cutting dominates accompanied by limited brittle fracture under larger depths of cut and lower scratch velocities. Cracking appears under larger normal scratch forces and lower scratch velocities. It was also shown that a compaction layer always exists after machining the thickness of which increases with an increasing of the normal force.